(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article presents data from the examination of 88 children under 14 years of age. It was found that intestinal infections of Proteus etiology are more common in young children, especially in those with altered reactivity and an unfavorable premorbid background. The course of the disease tends toward widespread lesions of the gastrointestinal tract, such as enteritis, enterocolitis, and gastroenterocolitis, occurring in severe forms with significant disturbances in water-electrolyte balance. The severity of the patient’s condition correlates with the intensity of the diarrhea lsyndrome.